Forty Years of Islamic Economics Research: A Bibliometric Review and Future Research Agenda - Ratna Ratna (Program Studi Ekonomi Syariah, 2026)
This study maps forty years of Islamic economics research and develops a future research agenda using a PRISMA-adapted bibliometric review. A Scopus search for “Islamic economics” OR “sharia economics” identified 889 records; 849 remained after the documented year criterion, 577 were journal articles, and 546 met the final inclusion criteria. Structured bibliographic summaries were available for 543 articles and were analyzed for publication year, source, authorship, and title-term patterns. Results show a formative stage before 2005, strong expansion after 2015, and marked acceleration after 2020, with 281 records published during 2021-2025. The literature is concentrated in specialized outlets led by Journal of King Abdulaziz University, Islamic Economics. Finance, banking, law, systems, and social concerns remain central, while waqf, social reporting, halal value chains, sustainability, blockchain, FinTech, and entrepreneurship indicate genuine diversification. The review concludes that Islamic economics has moved beyond a normative project but remains finance-centered, methodologically uneven, and insufficiently integrated with development and sustainability research. Future work should connect maqāṣid and ethical claims to measurable socioeconomic outcomes through comparative, interdisciplinary, and methodologically transparent designs.